The geography of you and me ebook - Smith, Jennifer E. (2014)
Lucy lives on the twenty-fourth floor. Owen lives in the basement. It's fitting, then, that they meet in the middle — stuck between two floors of a New York City apartment building, on an elevator rendered useless by a citywide blackout. After they're rescued, Lucy and Owen spend the night wandering the darkened streets and marveling at the rare appearance of stars above Manhattan. But once the power is back, so is reality. Lucy soon moves abroad with her parents, while Owen heads out west with his father. The brief time they spend together leaves a mark. And as their lives take them to Edinburgh and to San Francisco, to Prague and to Portland, Lucy and Owen stay in touch through postcards, occasional e-mails, and phone calls. But can they — despite the odds — find a way to reunite? Smartly observed and wonderfully romantic, Jennifer E. Smith's new novel shows that the center of the world isn't necessarily a place. Sometimes, it can be a person.